Valdosta Project Change, Scrapbook, September 1999 - Valdosta Project Change (Lowndes County Historical Society, 1999)
9/1- Affirmative Action may be losing ground- Rebecca Yull; 9/1- Where will the people go? - Freddie L. Sirmans Sr., Valdosta; 9/3- Questions Remain: Tribunal challenges official version of inmate death- Brian Lawson; 9/5- Tense Moments: March by People’s Tribunal ends in prayer after brief encounter with law enforcement- Brian Lawson; 9/9- We must learn to respect all people- William M. Eanes, Valdosta; 9/9- Marchers ‘in control’ of Saturday event- Mark George, Albuquerque NM; 9/9- Weed and Seed funds run dry: Budget delay halts ‘Granny’s House’ program and community policing efforts- Brian Lawson; 9/21- Second white supremacist guilty in black man’s dragging death- Associated Press;
Valdosta Project Change. “Valdosta Project Change Scrapbook, September 1999,” Lowndes County Historical Society. Valdosta State University Archives and Special Collections, MS-181: Valdosta Project Change Scrapbook Collection, 1997-2003. 1 PDF and scans, 8 pages. 428 MB (448,899,256 bytes).
Keywords: Clippings (Books, newspapers, etc.); Discrimination--Prevention; Lowndes County Historical Society (Valdosta, Ga.); Nonprofit organizations; Project Change; Race discrimination--Prevention; Racism; Scrapbooks; Valdosta (Ga.) -- Social conditions; Valdosta (Ga.); Valdosta Daily Times; Valdosta Project Change